If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -5x + 4x = 6 Combine like terms: -5x + 4x = -1x -6 + -1x = 6 Solving -6 + -1x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 6 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 6 + 6 -1x = 6 + 6 Combine like terms: 6 + 6 = 12 -1x = 12 Divide each side by '-1'. x = -12 Simplifying x = -12
| 3x+30=x+14 | | -12+2x+x=24 | | -14+14v=-10 | | 2(x^2+3x+10)=0 | | (13a^2-6a^5-2a)-(10a^2-11a^5+9a)= | | x+3x-27=25 | | -2x+4x-3=9 | | -3y+9=-2(3y+6) | | -4x+2x-17=9 | | 10x+29=4x+173 | | x-41-6x=29 | | 5a+(8+a)= | | 6*6*6*6*6= | | x^2+x-1=9 | | 6x-4x-9=15 | | 3x+10-x=9+4x-5 | | 15a+4b=66 | | 21z^2+85z-28=0 | | 8*7*6*5*4*3*2= | | 2g^2-g-6=0 | | Givenb(x)=[x+4]Whatisb(-10) | | 5=-2+27 | | 9+7x=9+x | | 12+10y=32 | | 9x-15=12x-6 | | 2x-45=-5 | | 0=(2a+1)(a-1) | | 6x-15+4=31 | | 6x-3=8x-6-4 | | 2x+60=6x-8 | | 5x^2+55x=120 | | -3(2x+7)-5(x-3)=12x+15 |